Synthesis, characterization and an application of graphene oxide nanopowder: methylene blue adsorption and comparison between experimental data and literature data - Cigeroglu, Zeynep; Hasimoglu, Aydin; Ozdemir, Oguz Kaan (TAYLOR & FRANCIS INC, 2021)
With the discovery of graphene, the necessary synthesis studies have been carried out for the use of graphene oxide (GO) as an adsorbent to remove toxic materials. In this study, GO nanopowder was synthesized to conduct methylene blue (MB) adsorption studies. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) characterization tests were used to investigate the adsorbent structure. The highest adsorption capacity was found to be 311.74 mg/g under the optimal conditions (0.5 g L-1 of adsorbent dose at 100 rpm mixing the speed of shaking bath, pH 10, and 25 degrees C). Kinetic mechanism and isotherm models were applied to experimental data. Pseudo-second-order kinetic model was a well fit to our experimental data. Besides, thermodynamic study revealed that adsorption process was spontaneous and exothermic. Moreover, adsorption capacity of GO nanopowder was compared to other graphene and functionalized graphene oxide for MB from aqueous solutions.
Keywords: Graphene oxide nanopowder; methylene blue; thermodynamic; adsorption; PHYTOGENIC MAGNETIC NANOPARTICLES; AQUEOUS-SOLUTION; FUNCTIONALIZED GRAPHENE; DYE ADSORPTION; CHITOSAN/GRAPHENE OXIDE; EFFECTIVE ADSORBENTS; ENHANCED ADSORPTION; EFFICIENT REMOVAL; ACTIVATED CARBON; HIGHLY EFFICIENT; Chemistry